The daily dad : 366 meditations on parenting, love and raising great kids - Holiday, Ryan (Portfolio/Penguin, 2023)
"A thoughtfully curated daily devotional full of inspiring quotes and advice, from the bestselling author of THE DAILY STOIC-for any dad as they navigate the most important journey of their life What does it mean to be a great father? And then, how do you become one? Parenting is a role filled with incredible meaning and purpose, one that men have a responsibility to take seriously. But every father needs guidance. Men need someone to inspire and challenge them to go the distance, because being a parent is something you do every day. Instead of a parenting book you read one time as a sleep-deprived new parent (and instantly forget among all the other things you're now supposed to remember), THE DAILY DAD provides 366 accessible meditations on fatherhood, a manageable slice for each day. From bestselling author Ryan Holiday, a father of two himself, this daily devotional will help dads old and new to find inspiration and advice on a day-to-day basis in the lifelong job of being a dad. Drawing quotes from history, pop culture, literature, and psychological research, each entry will provide a memorable lesson on being the role model your child needs, rooted in timeless principles. From Socrates to Martin Luther King Jr., Jerry Seinfeld to Jesus, THE DAILY DAD will draw on wisdom from mothers and fathers, heroes and celebrities, ancient philosophy and contemporary figures, in order to help each dad face the daily challenges of parenting, and ultimately become the best father they can be"--